Biostratigraphical and sedimentological study of an Upper Cretaceous succession in the Sami area (central area of Kefallinia, W. Greece) - Zoumpouli, E.; Pomoni-Papaioannou, F.; Zelilidis, A.; Iliopoulos, G. (Bulletin of the Geological Society of Greece, 2013)
On the island of Kefallinia, which lies at the external edge of the Hellenides fold and thrust system, appear the Paxi and the Ionian Zones. In this study, an Upper Cretaceous carbonate succession, which is a part of the Paxi Zone, cropping out near the area of Sami (central area of Kefallinia), is discussed in detail with regard to its depositional facies, microfacies, biostratigraphy and palaeoenviroments. Detailed sedimentological and palaeontological investigations have been carried out on seven sections and petrographic analysis of thin-sections that led to the recognition of a number of microfacies types grouped into four facies zones. There was recorded a supratidal- intertidal (restricted)-intertidal (open lagoon)- subtidal (or shallow subtidal) vertical transition. Supratidal facies are characterized by fenestral and peloidal wackestone / packstone, intertidal (restricted) facies are represented by bioclastic wackestone and bindstone, whereas intertidal (open lagoon) facies are indicated by bioclastic packstone. Finally subtidal facies are dominated by bioclastic floatstone and grainstone. Benthic foraminifera are especially abundant and along with calcareous algae are the most important fossils used for age determination. The benthic foraminiferal genera that were identified (Cuneolina sp., Quinqueloculina sp., Nezzazata sp., Pseudonummoloculina sp., Dicyclina sp.), in addition with the observed calcareous algae, rudist and gastropods provide significant data for the depositional environments and the paleoecology of the Paxi Zone during the Upper Cretaceous.